\(a,\Rightarrow\left[{}\begin{matrix}2x-3=5\\3-2x=5\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=4\\x=-1\end{matrix}\right.\\ b,\Rightarrow\left|x-1\right|=1-3x\\ \Rightarrow\left[{}\begin{matrix}x-1=1-3x\\x-1=3x-1\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=\dfrac{1}{2}\\x=0\end{matrix}\right.\)
a) \(\Rightarrow\left[{}\begin{matrix}2x-3=5\\2x-3=-5\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}2x=8\\2x=-2\end{matrix}\right.\)\(\Rightarrow\left[{}\begin{matrix}x=4\\x=-1\end{matrix}\right.\)
b) \(\left|x-1\right|+3x=1\left(đk:x\le\dfrac{1}{3}\right)\)
\(\Rightarrow x-1=3x-1\)
\(\Rightarrow2x=0\Rightarrow x=0\left(tm\right)\)